Youth Unemployment in Mediterranean Countries - Werner Eichhorst; Franziska Neder (Institute for the Study of Labor (IZA), 2014)
In all Mediterranean countries youth unemployment has reached alarming record levels. This paper analyses the current situation in France, Greece, Italy, Portugal, and Spain. In all countries school dropout rates are high, returns to education are low and the transition from education to work is problematic and difficult. This is due to a poor working vocational training system, the dualization of the labor market and minimum wages that are set too high. The Great Recession deteriorated the situation of young people, but youth unemployment is mostly structural. To overcome this crisis the overall performance of the labor market has to be improved.
Keywords: J21; J23; J24; 330; youth unemployment; Mediterranean countries; Europe; vocational training